Rhabdomyolysis Induced by Simvastatin-diltiazem Interaction in Unrecognized Hypothyriodism: Case Report and Literature Review - Ran, Hai-Hong; Zhang, Ran; Lu, Cai-Yi; Gao, Wei; Huang, Ya; Gao, Yu-Ling; Yang, Qiong-Xiang (Journal of Physiological and Biomedical Sciences, 2010)
Simvastatin, the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, is widely prescribed to patients with hypercholesteremia and its muscular toxicity has been widely reported. The metabolism of simvastatin depends on the enzymic activity of cytochrome P450 3A4 (CYP3A4) and inhibitors of CYP3A4 can result in clinical events by interacting with simvastatin. Diltiazem is a moderate inhibitor of CYP3A4, which is known to increase the serum concentration of simvastatin. Our patient suffered from unrecognized hypothyroidism for a long time and had been stable for more than one year on low-dose simvastatin therapy of hypercholesteremia. However, rhabdomyolysis occurred with the addition of diltiazem. This is one of scanty reports of rhabdomyolysis induced by simvastatin-diltiazem drug interaction, but the first report in hypothyroid patient. This patient reminds the clinicians that although diltiazem as a moderate CYP3A4 inhibitor can be used cautiously with small doses of CYP3A4-dependent statins (e.g. simvastatin), these two commonly used drugs should be avoided in hypothyroid patient. Meanwhile, rhabdomyolysis induced by simvastatin-diltiazem drug interaction and its clinical significance is reviewed.